The Urgency of Information Technology and Village Administration Services (Study on SILDEKAN) - Hidayat, Zainul; Maulidah, Ulfa (Journal of Informatics Development, 2023)
This study aims to determine the urgency of the existence of Information and Communication Technology in various administrative and communication service applications at the village level in particular. This includes the planned presence of SILDEKAN (Digital Technology Application through Information System and Services of Babakan Village), Lumajang district. This is a departure from the various complaints from services that are still not as expected. This research uses the library research method (literature study), looking for relevant literature sources according to the topic discussed, with the aim of finding scientific studies on the use of service and information applications carried out by the village government including the planned use of SILDEKAN. In conclusion, the application of digital technology through the Babakan Village Information and Service System (SILDEKAN) in Babakan village, Padang sub-district, Lumajang, East Java to provide services and information is very urgent and needs to be implemented immediately as part of efforts to improve service quality.